2013
DOI: 10.1007/s12032-013-0536-5
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of platelet endothelial cell adhesion molecule-1 in non-small-cell lung cancer patients

Abstract: Our previous studies have shown that platelet endothelial cell adhesion molecule-1 (PECAM-1), a member of the immunoglobulin superfamily, is a critical mediator of anchorage-independent growth and anoikis resistance in lung carcinoma cells. The purpose of this study was to analyze the protein expression of PECAM-1 in non-small-cell lung carcinoma (NSCLC) tissues and its clinical significance in NSCLC patients. By immunohistochemical analysis, high microvessel density (MVD) of PECAM-1 was detected in the stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Moreover, some of the associated adjacent genes are implicated in cancer. For example, PIM3 is a proto‐oncogene that enhances pancreatic cancer growth by modulating tumor vasculogenesis (Kuang et al , ; Liu et al , ); PTP4A3 can promote cancer metastasis particularly in colorectal cancers (Al‐Aidaroos & Zeng, ; Cramer et al , ; Huang et al , ); and TOMM20 expression is associated with tumor size in gastric cancer (Zhao et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some of the associated adjacent genes are implicated in cancer. For example, PIM3 is a proto‐oncogene that enhances pancreatic cancer growth by modulating tumor vasculogenesis (Kuang et al , ; Liu et al , ); PTP4A3 can promote cancer metastasis particularly in colorectal cancers (Al‐Aidaroos & Zeng, ; Cramer et al , ; Huang et al , ); and TOMM20 expression is associated with tumor size in gastric cancer (Zhao et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies had reported that CDH5 expression is associated with multiple tumors [ 43 , 44 ], such as gastric cancer and breast cancer, but the relationship between CDH5 and LUAD is still to be determined. PECAM1 is a multifunctional cell adhesion molecule involved in numerous physiologic processes within the vasculature; Abraham et al found that the activity of PECAM1 appears to be associated with the tumor microenvironment and tumor cell proliferation [ 45 ]; Kuang et al demonstrated that PECAM1 could be a potential prognostic factor and therapeutic target in NSCLC [ 46 ]. The von Willebrand factor (VWF) is a multimeric glycoprotein and plays an essential role in mediating platelet-tumor cell interactions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PECAM1 is involved in LUAD tumourigenesis by regulating the expression of vascular endothelial growth factor. In fact, it can maintain and restore vascular integrity and is commonly used as a marker for angiogenesis 28,32 .…”
Section: Discussionmentioning
confidence: 99%